Low-symmetry distortions in Extended Metal Atom Chains (EMACs): Origins and consequences for electron transport - Georgiev, V; Mohan, P; DeBrincat, D; McGrady, J (2013)
The extended metal atoms chains (EMACs) constitute a diverse group of molecules differing in both length and identity of the constituent metal ions. They therefore present important challenges to our understanding of metal-metal bonding and its relationship to structural, magnetic and electron transport properties. In this review we summarise our current understanding of the origins of low-symmetry distortions in these chains and their impact on current flow through the molecule. We conclude that structure, magnetochemistry and resistance are all intimately related through a shared dependence on the energies and orientations of the frontier orbitals. © 2012 Elsevier B.V..